2014
DOI: 10.1016/j.peptides.2014.06.003
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of cell volume and water transport – An old fundamental role of the renin angiotensin aldosterone system components at the cellular level

Abstract: The expression and the role of renin angiotensin aldosterone system (RAAS) components on regulation of cell volume and water transport on vertebrates and invertebrates were reviewed. The presence of these components even in simple organisms like leeches and their relevance for the control of cellular volume and water transport supports the view that the expression of these components, at cellular level, is an acquisition which was preserved throughout evolution.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 38 publications
1
5
0
Order By: Relevance
“…37 Similarly, to ACEi treatment, the pathway Ang II/Ang III/AT2-R is also still operative. Thus, even in the event ACEi or ARB are used during the inflammatory phase of SARS-CoV2 pneumonia and ARDS, redundant alternative pathways exist for the activation of AT2 receptors or Mas Receptors [via Angiotensin (1)(2)(3)(4)(5)(6)(7)] to maintain the anti-inflammatory capacity and counteract the cytokines storm (Figure 2B). AT2-R activation counteracts most effects of AT1R by inhibiting cell proliferation and differentiation, promoting vasodilation, and reducing inflammation and oxidative stress.…”
Section: Does the Treatment With Either Acei Or Arbs Facilitate Sars-cov-2 Infectivity?mentioning
confidence: 99%
See 1 more Smart Citation
“…37 Similarly, to ACEi treatment, the pathway Ang II/Ang III/AT2-R is also still operative. Thus, even in the event ACEi or ARB are used during the inflammatory phase of SARS-CoV2 pneumonia and ARDS, redundant alternative pathways exist for the activation of AT2 receptors or Mas Receptors [via Angiotensin (1)(2)(3)(4)(5)(6)(7)] to maintain the anti-inflammatory capacity and counteract the cytokines storm (Figure 2B). AT2-R activation counteracts most effects of AT1R by inhibiting cell proliferation and differentiation, promoting vasodilation, and reducing inflammation and oxidative stress.…”
Section: Does the Treatment With Either Acei Or Arbs Facilitate Sars-cov-2 Infectivity?mentioning
confidence: 99%
“…It is involved in the regulation of cardiovascular, metabolic and immune-regulatory homeostasis. 1 The Severe Acute Respiratory Syndrome-Coronavirus (SARS-CoV) and Severe Acute Respiratory Syndrome-Coronavirus-2 (SARS-CoV-2) utilize the ACE2-Receptor (ACE2-R) to invade human cells in alveolar epithelial and in several other tissues where ACE2-R is expressed. [2][3][4] SARS-CoV-2 infection is triggered by binding the spike S protein of the virus to ACE2.…”
Section: Introductionmentioning
confidence: 99%
“…The expression of certain RAAS components even in simple organisms like crustaceans, insects, and leeches underscores the importance of the renin cascade in the control of cell volume and water homeostasis throughout evolution (De Mello 2014). The history of the RAAS and its discovery has recently been retraced with great accuracy in a review paper by Tsukamoto and Kitakaze (2013).…”
Section: A Complex and Highly Regulated Machinerymentioning
confidence: 99%
“…Evidence provided in recent decades revealed that local expression of renin angiotensin or aldosterone impairs communication between heart cells by altering the gap junction conductance ( 20 24 ). Angiotensin II, for instance, plays an important role on the modulation of cell communication, inward calcium current, heart contractility, and cell volume regulation in health and disease through activation of cell surface AT1 receptors as well as PKC or tyrosine kynases ( 22 , 24 , 25 ).…”
Section: Raas Metabolic Cooperation and Organogenesismentioning
confidence: 99%
“…Evidence is now available that the formation of angiotensin ( 1 3 , 8 , 9 , 12 , 20 ) [Ang (1–7) elicited by the activation of ACE2 ( 39 )] has beneficial effects in the heart ( 39 , 41 , 42 ), counteracting the harmful effects of Ang II ( 43 ) and re-establishing impulse conduction during myocardial ischemia ( 42 ) as well as after cell swelling ( 44 ). It is then conceivable that Ang (1–7) can play a role in the formation of functional cellular patterns in the adult heart by enhancing gap junction permeability with consequent improvement of metabolic cooperation between cardiac cells.…”
Section: Ace/ang Ii/at1 Receptor Axis Versus Ace2/ang(1-7)/mas Receptmentioning
confidence: 99%